Akayet Inra Patra = Hikayat Inra Patra - Po Dharma; Abdul Karim; Moussay, Gérard (Kuala Lumpur Perpustakaan Negara Malaysia dengan kerjasama l'Ecole franc̲aise d'Extrême-Orient, 1997)
Cham classic literature and manuscript.
Title also in Cham characters.
Includes bibliographical references and index.
In Cham (roman and script), with preface, and introduction in Malay and French.
Keywords: Manuscripts, Cham; Cham literature -- History and criticism